Land‐atmosphere coupling in EURO‐CORDEX evaluation experiments. Issue 1 (7th January 2017) - Knist, Sebastian; Goergen, Klaus; Buonomo, Erasmo; Christensen, Ole Bøssing; Colette, Augustin; Cardoso, Rita M.; Fealy, Rowan; Fernández, Jesús; García‐Díez, Markel; Jacob, Daniela; Kartsios, Stergios; Katragkou, Eleni; et al.
Abstract: Interactions between the land surface and the atmosphere play a fundamental role in the weather and climate system. Here we present a comparison of summertime land‐atmosphere coupling strength found in a subset of the ERA‐Interim‐driven European domain Coordinated Regional Climate Downscaling Experiment (EURO‐CORDEX) model ensemble (1989–2008). Most of the regional climate models (RCMs) reproduce the overall soil moisture interannual variability, spatial patterns, and annual cycles of surface exchange fluxes for the different European climate zones suggested by the observational Global Land Evaporation Amsterdam Model (GLEAM) and FLUXNET data sets. However, some RCMs differ substantially from FLUXNET observations for some regions. The coupling strength is quantified by the correlation between the surface sensible and the latent heat flux, and by the correlation between the latent heat flux and 2 m temperature. The first correlation is compared to its estimate from the few available long‐term European high‐quality FLUXNET observations, and the latter to results from gridded GLEAM data. The RCM simulations agree with both observational datasets in the large‐scale pattern characterized by strong coupling in southern Europe and weak coupling in northern Europe. However, in the transition zone from strong to weak coupling covering large parts of central Europe many of the RCMs tend to overestimate the coupling strength in comparison to both FLUXNET and GLEAM. The RCM ensemble spread is caused primarily by the different land surface models applied, and by the model‐specific weather conditions resulting from different atmospheric parameterizations. Key Points: Spatial patterns, seasonal cycles, and interannual variability of coupling related soil moisture and surface fluxes are reproduced EURO‐CORDEX RCMs agree in large‐scale weak and strong coupling regimes while there is large variability in the transition zone In comparison to FLUXNET and GLEAM data the RCMs show a clear tendency toward overestimating coupling strength